Makna Denotasi dan Konotasi dalam Lirik Lagu Garam Dan Madu (Sakit Dadaku) Karya Tenxi, Naykilla, & Jemsii (Kajian Semiotika Roland Barthes) - Muhammad Ryan; Dwi Wahyu Candra Dewi (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study examines the denotative and connotative meanings contained in the lyrics of the song Garam dan Madu (Sakit Dadaku) by Tenxi, Naykilla, and Jemsii, which raises the theme of doubt and longing for love. The purpose of the study is to reveal the literal meaning and implied meaning in the lyrics. The method used is descriptive qualitative with data in the form of song lyric texts obtained from official sources. The results of the study show that the lyrics of this song contain other complementary meanings, namely the denotative meaning describes doubt, longing, uncertainty, and a promise to give the best in their relationship while the connotative meaning contains deeper emotions and symbolism related to love, hope, and commitment. This study provides an in-depth understanding of the song's message and its contribution to the study of semantics and popular culture.